DETERMINANTS OF DISEASE EVENTS IN WASTE TRANSPORT OFFICERS IN THE ENVIRONMENT AND FORESTRY OF KENDARI CITY - arimaswati arimaswati; Nasrul Nasrul; La Ode Alifariki (STIKes Hang Tuah Pekanbaru, 2020)
Background: Worm infections occurs in people who pay little attention to personal hygiene behavior, home sanitation and lack of knowledge about worms infection diseases. Objective: This study aims to determine the related factors associated with worms infections incidences in garbage collector of the Environtmental and Forestry Department, Kendari. Method: This research used analytic observational with cross sectional study design. Determination of the sample in this study used the total sampling approach. The sample in this study is 45 garbage collector. Data collection by used questionnaires and microscopic examinationt identifyti the presence of worm infections in garbage collectors. From the sample examination, we have known that 6 out of 45 respondent were infected by worms. The statistical test used was chi square at an alpha error level of 0.05. Results: The worms infected the respondent are the Ascaris lumbricoides and the Trichuris trichiura species from the STH group.The result shows that there is correlation between personal protective device usage with the occurrence of worms infection (Ï = 0,012), there is correlation between hand washing habit with the occurrence of worms infection (Ï = 0,023), there is correlation between the bowel habits with the occurrence of worms infection (Ï = 0,023). Conclussion: From this study, it can be concluded that there is a correlation between behavioral and home environment sanitation knowledge with the occurrence of worms infection incidences in garbage collectors of the Environmental and Forestry Department